The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jfpe.13222
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of chestnut and fat/oil contents in cocoa chestnut cream production—A new product development

Abstract: The textural, rheological, and sensory characteristics of cocoa chestnut cream containing different fat/oil and chestnut ratios were examined within present research. Two different chestnut (7.5 and 10%) and fat/oil ratios (25.75 and 28.25%) were used in laboratory scale model manufacturing. As the rate of chestnut increased, accelerated oil separation and yield stress values increased, conversely stickiness, apparent viscosity, plastic viscosity, consistency index values, and body‐texture score decreased. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…During the storage time, there was an increase in PV for all samples used in this work. The pure olive oil after 2 months showed a PV of 1.468 meq O 2 •kg −1 that agrees with previous studies [30]. Nevertheless, this result is also well below the defined limit in the European Union for PV of extra virgin olive oil (<20 meq O 2 •kg −1 ) and the limit for peroxide value in edible fats (<10 meq O 2 •kg −1 ), indicating a good oxidative stability of the organogels, considering both the production method and storage conditions of the developed organogels [31,32].…”
Section: Oxidative Stabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…During the storage time, there was an increase in PV for all samples used in this work. The pure olive oil after 2 months showed a PV of 1.468 meq O 2 •kg −1 that agrees with previous studies [30]. Nevertheless, this result is also well below the defined limit in the European Union for PV of extra virgin olive oil (<20 meq O 2 •kg −1 ) and the limit for peroxide value in edible fats (<10 meq O 2 •kg −1 ), indicating a good oxidative stability of the organogels, considering both the production method and storage conditions of the developed organogels [31,32].…”
Section: Oxidative Stabilitysupporting
confidence: 92%
“…Some of the more important properties regarding sensory perception of spreadable products are firmness and spreadability, which were found to have a wide range of values, showing tailoring potential for a wide range of spreadable products, including, as seen above, butter [ 2 , 3 , 11 , 12 ]. It is important to notice that this result does not exclude the other samples from being used for other food applications, as different products will have different functional needs and properties [ 30 , 33 , 34 , 35 , 36 ]. Alvarez et al (2011) determined the firmness of mashed potatoes to be around 6 N, Sanders et al (2014) determined a value of around 9 N for peanut butter, while Hadnadev et al (2011) found the firmness of edible vegetable fat to be as low as 5 N, and Nikolić et al (2014) analysed the spreadability of low-fat food spreads made from hull-less pumpkin seed flour and reported values in the same range as those described in this work, thus demonstrating the potential for the applicability of different organogels in the food industry [ 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similarity was observed between stickiness and spreadability characteristics. Aydemir and Atalar (2019) found the same profile in cocoa chestnut creams. increased, the yield stress value increased significantly at all cocoa carob creams (p < .05).…”
Section: Textural Characteristicsmentioning
confidence: 55%
“…Aydemir (2019a) reported that AOS values in commercial cocoa hazelnut creams ranged from 7.40% to 8.87%. Aydemir and Atalar (2019) found 5.93%-8% AOS in cocoa chestnut creams.…”
Section: Accelerated Oil Separationmentioning
confidence: 92%
See 1 more Smart Citation